Minority at home and abroad: The Islamic theory and its challenge - Moniruzzaman, Md. (2019)
The Islamic minority laws were developed more than a millennium ago. Since then social, political and legal composition and structure of the society have drastically changed. The modern state-system is based on the ideas of universal citizenship with equal socio-political, economic and legal rights. The modern nation-states are multiethnic, multicultural and multireligious. The classical Islamic minority laws are clearly short of universal citizenship. A second issue is the Muslim minority abroad in a non-Muslim state where they face the dilemma of enjoying universal citizenship rights and following Islamic code of dressing. This second issue gives rise to a conflict between local municipal laws and Islamic universal shari’ah laws. The compatibility of Islamic political order in the modern state system depends on its ability to address this fundamental issue. This article highlights on two issues namely- the question of minorities in a Muslim state, and the question of Muslim minority in non-Muslim majority states.